Locating the Lost Gupta Period Ramayana Reliefs from Katingara, Uttar Pradesh - Greaves, Laxshmi Rose (Religions of South Asia, 2018)
This article collates a fascinating group of early fifth-century ce terracotta temple reliefs, some bearing short Brahmi inscriptions. The panels entered numerous museum and private collections in India and abroad from the 1960s and early 70s. Of the panels, which comprise animated narrative scenes, amorous couples, lesser-divinities and composite creatures, it is those depicting episodes of the Sanskrit epic Ramayana that this article is specifically concerned with. Although the images share a bold, idiosyncratic style, and a likeness in scale, material and finish, they have never been acknowledged as having a shared origin, with most being loosely described as hailing from Uttar Pradesh. The central aims of this article are to analyse the iconography of this remarkable collection of panels and to put forward an argument for their place of origin being a small archaeological site near the village of Katingara, located in the alluvial plains beside the Kali Nadi river (a tributary of the Ganges) in District Etah, Uttar Pradesh. Katingara will also be positioned within the context of recorded early archaeological sites in the region. Importantly, the panels constitute one of the earliest and most extensive collections of terracotta Ramayana images surviving from the Gupta period, and this is the first time since their illicit removal from Katingara that they have been 're-assembled'.